Stock Market Liberalisation And Cost Of Equity: Firm-Level Evidence From Malaysia - Swee, Sim Foong; Kian, Ping Lim (Asian Academy of Management (AAM), 2016)
This study extends the stock market liberalisation literature by conducting a firm-level analysis on the emerging economy of Malaysia. Using a finer measure of foreign ownership, we explore the association between liberalisation and cost of equity for public listed firms on Bursa Malaysia over the sample period of 2002-2009. We find strong support for our hypothesis that total foreign ownership is negatively and significantly associated with cost of equity. Further disaggregate analysis suggests foreign institutions that trade through direct accounts are driving the lower cost of equity. When the model is extended to include interaction term, we find that an effective board of directors further strengthens the negative relationship between foreign institutions and cost of equity. Our empirical results consistently support the corporate governance channel in which foreign institutions play an active monitoring role.